Soil water characteristic curve and shear strength of soil with bimodal characteristic - Nio, Alfrendo Satyanaga (2015)
Many residual and colluvial soils show bimodal grain-size distribution (GSD). Some soils with bimodal characteristic of GSD result in bimodal characteristic of soil-water cahracteristic curve (SWCC), whereas others result in unimodal characteristic of SWCC. Modelling GSD and SWCC with a continuous function is advantageous. The GSD model can be used to classify the soil and predict the SWCC. On the other hand, the SWCC model can be used to obtain soil properties, such as: the air-entry value, residual water content and water-entry value. Many research works have been carried out on development of GSD and SWCC model. However, most of them were limited to soils with unimodal characteristics. The objective of this research is to study the mechanical behaviour of unsaturated soil, particularly the SWCC and shear strength of the unsaturated soil with bimodal characteristics. Several mathematical equations were proposed in this study, such as: the equations for best fitting the GSD, SWCC and shear strength of the unsaturated soil with bimodal characteristics, the equations for estimating the SWCC of soil with bimodal GSD and the equation for estimating the bimodal shear strength of the unsaturated soil. SWCC tests and unsaturated consolidated drained triaxial tests were carried out on nine different sand-kaolin mixtures which were compacted on dry density associated with wet of optimum (95% maximum dry density), optimum water content and dry of optimum (95% maximum dry density). The SWCC test results showed that the specimen with bimodal GSD does not always produce bimodal SWCC, but they can also produce unimodal SWCC, depending on soil density, void ratio, water content and ratio of coarse to fine particles within soil specimen. The specimen with bimodal GSD and consists of high percentage of fine particles is likely to have unimodal SWCC. This happens since the percentages of small pores are much higher that those of big pores within this soil specimen. In addition, the saturated water content of this soil specimen will be higher than the saturated water content of the soil specimen with bimodal GSD, but consists of low percentage of fine particles. The specimen with bimodal GSD and high dry density will contribute in the low air-entry value (AEV) and the steep slope of SWCC.